Proyeksi Pola Penyebaran Emisi Steam Boiler dan Genset PT J Dengan Pemodelan AERMOD - Tuhu Agung Rachmanto; Muhammad Fairuz Akmal (Prosiding ESEC, 2023)
The industrial world is growing rapidly over time, including PT J which is engaged in animal feed rations and meat processing. However, apart from producing products, the industry also produces waste products or emissions from supporting activities for the animal feed ration industry and meat processing. It is a challenge in itself to overcome so that the emissions produced do not exceed the environmental capacity around the PT J industrial area, as well as the suitability of the resulting emission value with the applicable regulations. The emission distribution modeling map is done by processing the emission data from the Steam Boiler unit and generator and then running the data in the AERMOD software. The results of running data using AERMOD show that the highest concentrations of emission distribution for parameters NOx and particulates are at a distance of 200-300 m with respective values of 38.3 µg/m3, and 10.4 µg/m3. Regarding to Appendix VII PP. No. 22 of 2021 concerning the Implementation of Environmental Protection and Management, it can be concluded that the environmental capacity for emission discharges from PT J's industrial location is still sufficient.